The role of the SGK3/TOPK signaling pathway in the transition from acute kidney injury to chronic kidney disease - Shu, Huapan; Wang, Yumei; Zhang, Hui; Dong, Qingqing; Sun, Lulu; Tu, Yuchi; Liao, Qianqian; Feng, Li; Yao, Lijun (Frontiers in Pharmacology, 2023)
Maladaptive repair of renal tubular epithelial cells (TECs) and aberrant accumulation of CD206+M2 macrophages are the key points in the transition from acute kidney injury (AKI) to chronic kidney disease (CKD). Nevertheless, the underlying mechanisms involved remain incompletely understood. Serum and glucocorticoid-inducible kinase3 (SGK3) is a serine/threonine protein kinase, required for intestinal nutrient transport and ion channels modulation. T-LAK-cell-originated protein kinase (TOPK) is a member of the mitogen-activated protein kinase family and is linked to cell cycle regulation. However, little is known about their roles in AKI-CKD transition. In this study, we revealed for the first time that SGK3 regulates TOPK phosphorylation to mediate TECs maladaptive repair, macrophage plasticity as well as the crosstalk between TECs and macrophages during AKI-CKD transition. Our results demonstrated that in different AKI-CKD mice models, the protein expression of SGK3 and p-TOPK were gradually inhibited in TECs, but enhanced in CD206+M2 macrophages. In vitro, SGK3 inhibition aggravated epithelial to meschymal transition (EMT) through reducing the phosphorylation state of TOPK, and controlling TGF-β1 synthesis and secretion in TECs. In addition, SGK3/TOPK axis activation promoted CD206+M2 macrophage polarization, which caused kidney fibrosis by mediating macrophage to myofibroblast transition (MMT). When co-cultured, the TGF-β1 secreted by maladaptive repaired TECs evoked CD206+M2 macrophage polarization and MMT, which could be attenuated by SGK3/TOPK axis inhibition in macrophages. Conversely, SGK3/TOPK signaling pathway activation in TECs could reverse CD206+M2 macrophages aggravated EMT. Taken together, our results demonstrate the inverse effect of SGK3/TOPK signaling pathway in EMT of TECs and CD206+M2 macrophages phenotype transition during the AKI-CKD transition. Therefore, targeted intervention with the SGK3/TOPK pathway in TECs and macrophages may serve as a novel therapeutic approach to ameliorate the AKI-CKD transition.